ANALYSIS OF THE INFLUENCE OF POLYGONAL WHEELS ON DYNAMIC PERFORMANCE OF A SIX-AXLE HEAVY FREIGHT LOCOMOTIVE (MT) - SUN XiaoJuan; SUN HongLiang; LI XingRen; WANG Yu (Jixie qiangdu)
With the increase of the load and running speed of heavy freight locomotives, the wheel wear becomes more and more serious, which can exacerbate the polygon formation of wheels. The influence of polygonal wheels on the dynamic performance of a wide-gauge six-axle heavy freight locomotive is examined, taking the ГОСТ standard as the main reference. The finite element model of the wheelset is established, and then a rigid-flexible coupling model is established by using the multi-body dynamics software. The polygonal wheel is described by the harmonic function. Effects of the parameters, unrounded amplitudes and polygon numbers are analyzed. The results show that the critical speed decreases because of the effect of the polygonal wheel. Within the design speed range of 120 km/h, the wheel polygon has little influence on the running comfort; the influence on the locomotive safety and the vehicle dynamic characteristics is closely related to the modal characteristics of the vehicle.